Determinants for participation in independent learning policy and independent campus programs - Gatot Gunarso; Lidia Sandra; Marcel Yap (International Journal of Evaluation and Research in Education (IJERE), 2023)
This paper proposes a framework for participation determinants in lifelong learning through the Independent Learning Policy and Independent Campus or Merdeka Belajar Kampus Merdeka/Independent Learning Independent Campus (MBKM). The framework is based on the technology acceptance model (TAM), self-determination theory (SDT), theory of planned behavior (TPB), and institutional theory. This study contributes to the literature by identifying specific factors and indicators to improve along with their impacts on the participation when the organizers of such initiatives wish to increase participation. Indonesia is the biggest country in South-East Asia with a large economy and influence in the world. Conditions, progress, and setbacks in Indonesia will influence other countries. Many job applicants do not meet the requirements for the job they applied for. Therefore, the Indonesian Ministry of Education initiated the MBKM programs to develop human quality, especially the university students to enhance their skills to meet the job requirements. The 740 respondents completed the online survey with 150 questions to represent reflective indicators. The results were analyzed with the partially least square-structural equation model (PLS-SEM) method and found the influential factors driving participation in MBKM are social influence, supporting factors, government decisions, utility, and recognition. further analysis indicated that convenience and financial incentive factors do not affect participation.